+0  
 
0
46
1
avatar

They  are both separate equations.

 

3p=9(27)q

 

log27-log2(11q-2p)=1

 Mar 3, 2020
 #1
avatar+21818 
+1

3^p = 3^2(27)^q

3p = 32 (33)q

3p= 32 (33q)

3p = 3(2+3q)

   so   p = 2 + 3q

 

log27 - log2 (11q-2p) = 1     sub in    p = 2 + 3q

log27 - log2 (11q-4-6q) = 1

log27 - log2 (5q-4) = 1                        convert to log10

log 7 /log2  - log(5q-4)/log2 = 1

log 7 - log (5q-4) = log2

log (5q-4 ) = log2 - log 7

5q-4 = .2857

q=.857142          then p = 4.571429                       

 Mar 3, 2020
edited by ElectricPavlov  Mar 3, 2020

43 Online Users

avatar
avatar
avatar
avatar
avatar
avatar
avatar